(untitled) (Revista de Ciências Agroveterinárias, 2002)
Phytophthora capsici damping-off and fruit rot of cucurbits is a serious proble m on rainy warm summer seasons at the highlands of Santa Catarina State, Brazil. The main goal of this study was to evaluate the effects of chicken manure and pine bark as soil amendments on cucumber (Cucumis sativus cv. ‘Caipira’) damping-off. The experiments were conducted under greenhouse (CAV/UDESC, Lages/SC) conditions in a completely randomized block design with seven to eight replications. The doses of chicken manure used were 0, 5, 10, 20, 30, 40, 50, and 60 g/kg of soil (6 kg/m2), and the doses of pine bark were 0, 5, 10, 20, 30, 40, and 50 g/kg of soil. Chicken manure at the dose of 60 g/kg significantly decreased damping-off of cucumber and significantly increased: (a) the total population of bacteria 60 days after soil amendment; (b) the amounts of N, P, and K in soil 120 days after soil amendment; (c) the soil pH at 30 and 120 days after soil amendment; (d) the number of healthy plants 30 days after sowing; and (d) the fresh plant weight 30 days after sowing. Pine bark increased significantly: (a) the bacterial population 30 days after soil amendment in the soil; (b) the population of Trichoderma spp. in the soil 60 days after soil amendment; and (c) the soil pH 30 days after soil amendment. On the second cucumber planting, only chicken manure at the dose of 60 g/kg reduced the amount of damping-off.